Three Women, Three Roots, Three Times, One Tree: Some Thoughts for Potential Gardeners - Gunnell, Terry (Religionsvidenskabeligt Tidsskrift, 2022)
ABSTRACT: This article considers the potential connections between the three nornir mentioned in Vǫluspá and the three roots of Yggdrasill mentioned in Grímnismál st. 31 and Gylfaginning which, like the nornir themselves, may have been seen (by some) as being connected with time. This raises the possibility that, at some point and for some people, the jǫtnar were closely connected with the world of death and the underworld (which, for some, may have been associated with the east from whence the sun rises). It also raises questions about whether Urðr should be seen as referring to the past, rather than the future, and reconsiders the earlier posited idea that life, death and time were seen as being a circular process much like the natural year. RESUME: Denne artikel omhandler den potentielle forbindelse mellem de tre nornir, der nævnes i Vǫluspá, og Yggdrasills tre rødder, der nævnes i Grímnismál st. 31 samt Gylfaginning. Ligesom nornerne selv kan de tre rødder være blevet set (af nogle) som forbundet med tid, hvilket kan betyde, at jætterne, i nogles øjne, var tæt forbundet med dødsriget og underverdenen (der, for nogle, kan have været associeret med retningen øst, hvor solen står op). Det åbner ligeledes for den mulighed, at Urðr snarere skal ses som forbundet med fremtiden, ikke fortiden. Artiklen genovervejer også en tidligere fremsat teori om, at livet, døden og tiden blev set som cirkulære processer på samme måde som årets gang.